The role of mindfulness in enhancing athletic performance: a critical review of empirical studies - Erinda Dwimagistri Sukmana; Agus Rianto; Ilham Kauli; Salmin Salmin; Rachmad Kristiono Dwi Susilo; Sutawi Sutawi; Gusti Pirandy (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Athletes face increasing psychological demands, making mental preparedness as vital as physical training in competitive performance.